The Meaning of Social Support and Self-Acceptance in Building Psychological Well-Being: An Interpretative Phenomenological Analysis Study of HIV Outreach Workers Who Are Survivors of Sexual Violence - Riska Riska; Rifqi Farisan Akbar; Prinska Damara Sastri (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Sexual violence experienced by HIV outreach workers can be traumatic and negatively impact the victim's psychological well-being. Lack of social support from the surrounding environment and workplace can leave victims feeling neglected, unprotected, and struggling to accept themselves. This low self-acceptance subsequently impacts the victim's psychological well-being after experiencing sexual violence. This study employed a qualitative method with an Interpretative Phenomenological Analysis (IPA) approach, aimed at deeply understanding the participants' subjective experiences of the phenomenon under study. The subjects in this study were four HIV outreach workers who had experienced sexual violence while carrying out their work. Data collection was conducted through in-depth interviews to explore the subjects' experiences, feelings, and meanings regarding the sexual violence. The results showed that the subjects experienced various psychological impacts, such as fear, stress, trauma, anxiety, overthinking, loss of work enthusiasm, and a tendency to withdraw from social circles. Furthermore, the lack of social support and low self-acceptance made the subjects' psychological recovery process more difficult and time-consuming. This study demonstrates that social support and self-acceptance play a crucial role in building the psychological well-being of HIV outreach workers who are survivors of sexual violence.